Collaboration in Focus: Photographic Evidence in the French Purge Trials, 1944–1949. Issue 3 (1st December 2022) - Lewis, Abigail E.
Abstract: This article examines the collaboration trials of French photographers André Zucca (1944–1945) and Robert Delhay (1947–1949) within the context of the postwar French state's attempts to punish collaboration and rehabilitate the French press. Paying attention to the interpretation of photographs as evidence, I argue that within the post–Liberation French courtroom, photographic evidence became crucial to narrating collaboration and resistance as a means of gaining re-acceptance into the profession and escaping legal charges. However, photographs proved too complicated to clearly prove either collaboration. Photographers disputed the charges against them by offering new interpretations of their photographs. These new readings were rooted in a postwar visual culture that had been saturated with photographs as historical evidence of Nazi atrocities, French victimization, and resistance. This article details how the collection and display of photographic evidence in these court proceedings informed the emergence of a postwar photographic press steeped in résistancialisme .